Survey and taxonomy of transmissions power control mechanisms for wireless body area networks - Fernandes, Duarte Manuel Azevedo (2018)
Wireless Body Area Networks (WBANs) comprise several sensor nodes equipped with a short range radio-frequency transceiver, implanted and/or attached to the human body. Their low form-factor and localization imply less resources available and limited energy capabilities. Therefore, energy efficiency of WBANs is a critical issue since, in many cases, batteries cannot be replaced or recharged, requiring mechanisms to extend their life-time. The aim of Transmission Power Control (TPC) mechanisms, which can be combined with other energy-saving mechanisms, is to reduce the energy consumption, external interferences and Specific-Observation-Rate (SAR) in wireless communications by dynamically adjusting the transmission power output of data transmission, with the minimum effect on other performance aspects, such as reliability and latency. This survey describes and analyses the TPCs developed as a result of a synergy created by two mechanisms, a Link Quality Estimator (LQE) and the Transmission Power Level (TPL) control. Design choices, in terms of the solutions devised to each mechanism, as well as, the strategy adopted to combine them in a TPC, are highlighted. A comparison between the newest and most relevant research works in this area is provided as a guideline to future research. A taxonomy to classify the different TPC mechanisms developed is proposed.